Risk factors associated with hypothalamic obesity after childhood - onset craniopharyngioma resection in a single center - PENG Xiao-jiao; GE Ming; WU Di; CAI Ying-jie; CHEN Jia-shu; LIANG Chen (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Objective To identify risk factors associated with hypothalamic obesity after craniopharyngioma resection in children. Methods The clinical data as well as imaging and operation details of 34 children with craniopharyngioma who met the inclusion criteria from June 2015 to September 2022 in Beijing Children's Hospital, Capital Medical University were collected for retrospective analysis. The body mass index (BMI) at last follow-up were recorded to identify hypothalamic obesity, univariate and multivariate Logistic regression analyses were used to screen the risk factors. Results A total of 47.06% (16/34) of children experiened hypothalamic symptoms, including obesity and increased appetite, lethargy and mood abnormalities after surgery. Logistic regression analysis showed that symptomatic endocrine abnormalities (OR = 31.453, 95%CI: 1.009-980.082; P = 0.049) and impairment of the hypothalamus of Puget Ⅱ grade (OR = 48.844, 95%CI: 1.053-2264.975; P = 0.047) were risk factors for postoperative hypothalamic obesity. Conclusions There is a high incidence of hypothalamic obesity after childhood - onset craniopharyngioma resection, symptomatic endocrine abnormalities and impairment of the hypothalamus of Puget Ⅱ grade are risk factors. Early identification of risk factors and early adoption of reasonable and effective interventon measures can improve the long-term quality of life in children.